Contributions of students of the modern language program to the group of protection to the tourism and national heritage Mebog (2017)
According to the nature of the National Police and taking as a basis the right to enjoyment of free time through tourism in secure environments, the General Law of Tourism "Law 300 of 1996", creates the Tourist Police, within the Directorate of Specialized Services of the National Police. Hierarchically the Tourist Police depends on the National Police and administratively depends on the Ministry of Commerce, Industry and Tourism. In this sense, Decree No. 4222 of November 23, 2006 "By which the structure of the Ministry of National Defense is partially modified" establishes in article 9 the functions of the Directorate of Protection and Special Services, giving it competence to guide and establish the necessary guidelines for the fulfillment of protection services for people, for the environment and natural resources, for children and adolescents, for tourists and for the archaeological, cultural and religious heritage of the nation.